Implementation science - Wilson, Paul M. (Cambridge University Press, 2022)
This Element introduces and critically reflects on the contribution of implementation science to healthcare improvement efforts. Grounded in several disciplines, implementation science is the study of strategies to promote the uptake of evidence-based interventions into healthcare practice and policy. The field's focus is threefold. First, it encompasses theory and empirical research focused on exploring, identifying, and understanding the systems, behaviours, and practices that influence successful implementation. Second, it examines the evaluation of strategies to address barriers or enablers to implementation in a given context. Last, it increasingly seeks to understand the process of implementation itself: what actually gets implemented, and when, why, and how? Despite the growing body of evidence, challenges remain. Many important messages remain buried in the literature, and their impact on implementation efforts in routine practice may be limited. The challenge is not just to get evidence into practice, but also to get implementation science into practice. This title is also available as Open Access on Cambridge Core.